Risk factor for gestational diabetes mellitus and impact of gestational diabetes mellitus on maternal and fetal health during the antenatal period - Jain, Uma; Singhal, Kusumlata; Jain, Shikha; Jain, Deepali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Gestational diabetes mellitus (GDM) is defined as any degree of dysglycaemia that occurs for the first time or is first detected during pregnancy. The adverse effects of GDM on pregnant women are pre-eclampsia, PIH, PPH, polyhydramanios, PROM, meanwhile, there would be an increase in dystocia, birth injury, and cesarean section Methods: This retrospective study was conducted in a Gynecology clinic in District Shivpuri to find out the various risk factors for GDM and to evaluate the impact of GDM on maternal and fetal health during the antenatal period. 84 patients who were diagnosed with GDM were included in the study. Results: Among risk factors; BMI >25 kg/m2 before pregnancy was found in 15.47% of the case, family history of diabetes mellitus 8.33%, Previous history of macrosomia 17.85%, Poor reproductive history 17.85%, baby with congenital malformation 8.33%, H/o unexplained IUFD 11.90%. H/o polyhydramnios 15.47%. History of PCOS 13.09% and preeclampsia was found in 17.85% of cases. In antenatal complications; miscarriages was found in 15.47%. polyhydramnios in 17.85%. Oligohydramnios in 8.33%, preterm labor in 11.90%, PROM in 9.52%, pre-eclampsia in 17.85%, sudden IUFD in 8.33% and congenital malformation was found in 4.76% of cases. On USG; IUGR was found in 7.14% of cases. Large for date fetus in 16.66% of cases and the normal growth was found in 76.19% of cases. Conclusions- In conclusion appropriate and timely diagnosis and treatment of GDM will result in decreased maternal and neonatal adverse outcomes comparable to general population rates, therefore, early diagnosis is important.